From infected to recovered: the mediating role of sleep quality between self-compassion, social support and COVID-19 psychosomatic symptoms - Outong Chen; Fang Guan; Chengqing Zhan; Ying Li (BMC Public Health)
Abstract Background Recent research has shown significant individual differences in COVID-19 psychosomatic symptoms. However, there has been a lack of studies investigating the influence of physical and psychological factors on these symptoms and their underlying mechanisms. This study aims to fill this gap by investigating the predictive role of self-compassion and social support on COVID-19 psychosomatic symptoms, as well as the potential mediating role of sleep quality. Methods Data were collected from 636 participants infected with COVID-19 during the early post-pandemic reopening phase in China. The measurement tools used in the current study included the Self-Compassion Scale, the Perceived Social Support Scale, Self-Rating Scale of Sleep, and a COVID-19 Psychosomatic Symptom Diary. Results A structural equation model revealed that: (1) social support directly predicts COVID-19 psychosomatic symptoms; (2) sleep quality fully mediates the relationship between self-compassion and COVID-19 psychosomatic symptoms; and (3) sleep quality partially mediates the relationship between social support and COVID-19 psychosomatic symptoms. Conclusions These findings not only confirm previous research but also provide new insights into the intricate interplay between psychological and physical factors and their influence on COVID-19 psychosomatic symptoms. The implications of these findings may inform the development of targeted rehabilitation programs in the post-pandemic era of the “new normal”. Clinical trial number Not applicable.